Elderly patients with comorbidities and acute coronary syndrome: primum non nocere? - Vives-Borràs, Miquel; Alessandro Sionis, and (REC, Interventional cardiology (Internet. English ed.), 2022)
According to data from the National Statistics Institute, life expectancy has increased from 73.5 years in 1975 to 83.6 years in Spain in the year 2019. Also, the mean age of the population has gone up 10 years during this same period.1 In this sense, the results from the study conducted by Dégano et al.2 in 2013 come as no surprise. They already anticipated a strong increase in the rate of acute coronary syndrome (ACS) within the next 35 years when the Spanish population > 75 years will represent almost a quarter of the national census. This study anticipated that between 2013 and 2049, the cases of ACS in elderly patients would increase over 70%, but keep a discrete growth in patients under 75 years. These data are but a glimpse of a not so distant future when our patients will be older and their life expectancy longer. Also, the association between aging and comorbidity means that we will have to treat more complex patients. Elderly patients with comorbidities are misrepresented in clinical trials studying the efficacy...